Heterologous production and functional characterization of: Bradyrhizobium japonicum copper-containing nitrite reductase and its physiological redox partner cytochrome c 550 - Cristaldi, Julio César (2020)
Two domain copper-nitrite reductases (NirK) contain two types of copper centers, one electron transfer (ET) center of type 1 (T1) and a catalytic site of type 2 (T2). NirK activity is pH-dependent, which has been suggested to be produced by structural modifications at high pH of some catalytically relevant residues. To characterize the pH-dependent kinetics of NirK and the relevance of T1 covalency in intraprotein ET, we studied the biochemical, electrochemical, and spectroscopic properties complemented with QM/MM calculations of Bradyrhizobium japonicum NirK (BjNirK) and of its electron donor cytochrome c550 (BjCycA). BjNirK presents absorption spectra determined mainly by a S(Cys)3pπ → Cu2+ ligand-to-metal charge-transfer (LMCT) transition. The enzyme shows low activity likely due to the higher flexibility of a protein loop associated with BjNirK/BjCycA interaction. Nitrite is reduced at high pH in a T1-decoupled way without T1 → T2 ET in which proton delivery for nitrite reduction at T2 is maintained. Our results are analyzed in comparison with previous results found by us in Sinorhizobium meliloti NirK, whose main UV-vis absorption features are determined by S(Cys)3pσ/π → Cu2+ LMCT transitions.